The Power of Partnership : Public and Private Engagement in Hydromet Services - World Bank (World Bank, Washington, DC, 2020)
The needs of societies for more accurate and reliable weather, climate, and hydrological ‘hydromet’ information are at the highest levels today. Weather events–including hurricanes, heat waves, floods, and droughts, jointly cause more economic damage and loss of life than any other disaster. Around the world, better warning systems, better meteorological and hydrological services, and customized service delivery can help prepare for and reduce the cost of weather events, minimize loss and damage, and build socio-economic resilience. Reliable hydromet services are in high demand in weather-dependent sectors like aviation, agriculture, shipping, transport, energy, and tourism. As the effects of climate change modify the patterns and intensity of natural hazards and as rapid urbanization and population growth increase vulnerability, adequate hydromet services are increasingly a very high value proposition. For over a decade, the World Bank has invested in the modernization of National Meteorological and Hydrological Services (NMHSs). Some countries have been more successful than others with sustaining and multiplying the outcomes of these investments. We have also witnessed that many countries are struggling to keep up with the ever-increasing demand for more sophisticated services to protect lives and assets as well as to support economies. Over the same decade, advances in technology and innovation have widened the scope of products and services that can be used to improve weather data, warning systems, and hydromet information. Private-sector actors are playing an important role and along with the academic community are helping to push the frontiers of knowledge, investing in innovative solutions that deliver more reliable forecasting and more efficient and diverse services. The dynamics between the public, private, and academic sectors have been evolving, creating more opportunities than ever to join forces to deliver the socio-economic benefits of a more informed and resilient world. This report looks at the current landscape of partnerships and analyzes the experience from eight countries that have explored different approaches to partnership as they seek to strengthen the provision of hydromet services. Not surprisingly, these experiences show that collaboration across public, private, and academic actors in this field is changing rapidly, can be complex and challenging but is worth the effort. The report offers ideas about lessons learned so far as countries attempt to structure a balanced model that builds on an awareness of comparative advantages, a shared commitment to improving global public goods in the service of strengthening global resilience.